Current sensor based on inline microfiber Mach–Zehnder interferometer - Jasim, A.A.; Harun, Sulaiman Wadi; Muhammad, M.Z.; Arof, Hamzah; Ahmad, Harith (Elsevier, 2013)
A compact inline microfiber Mach–Zehnder interferometer (MMZI) is proposed for current sensor application. The MMZI is fabricated using flame-brushing technique where both transition parts of a microfiber are tapered to reduce the waist diameter and form an interference region. The fabricated MMZI shows a good interference fringes with a high extinction ratio of 15 dB. The fringe spacing can be tuned from 3.95 nm to 3.36 nm as the length of the interference region is varied from 4.5 mm to 6 mm. The shift in the interference fringes is observed to be linearly proportional to the square of the amount of the flowing current and the slope efficiency of the sensor is obtained at 140.26 pm/A² with a correlation coefficient of 0.99. Since the refractive index of the fiber core has a different temperature coefficient than that of air, the interferometer can be used as a current sensor by placing the current carrying wire in contact with the waist region of the second part of the tapered fiber.